PENDAMPINGAN IMPLEMENTASI KESELAMATAN DAN KESEHATAN KERJA (K3) SEBAGAI UPAYA PENCEGAHAN KECELAKAAN KERJA DI PT. BALI MODA BUSANA KABUPATEN KARANGANYAR - Rohwiyati; Sulistya; Kim Budiwinarto; Juni Trisnowati; Yanti Sri Danarwati; Giarti Slamet; Praptiestrini; Dewi Pujiani; Sri Wahyu Ening Handayani (Surakarta Abdimas Journal, 2024)
The first activity carried out in this service activity was observation to determine problems in activities at PT Bali Moda Busana. Observations are only focused on the production department and some management staff. Based on the observations that have been made, it is found that the working environment at PT Bali Moda Busana, has the potential for physical hazards and the workers have not Personal Protective Equipment (PPE) at work which allows work accidents. The expected results in service activities are that employees in the production department have more knowledge about Occupational Safety and Health (K3); acquire knowledge of identifying potential hazards in the workplace and preventive measures for work accidents; and gain knowledge about the types of PPE (Personal Protective Equipment). Based on the results of this service activity in the form of counseling, training and mentoring that has been carried out; employees of the production department, to acquire knowledge about Occupational Safety and Health (K3); acquire knowledge of identifying potential hazards in the workplace and preventive measures for work accidents; and gain knowledge about the types of PPE (Personal Protective Equipment), then implement it in daily work, as the motto of work “Savety 1st”